Effects of mesyl salvinorin B alone and in combination with naltrexone on alcohol deprivation effect in male and female mice. (23rd April 2018) - Zhou, Yan; Crowley, Rachel; Prisinzano, Thomas; Kreek, Mary Jeanne
Highlights: Mesyl Salvinorin B (MSB) reduced alcohol "relapse" in male and female mice. Naltrexone reduced alcohol "relapse" in male and female mice. Synergistic blockade of alcohol "relapse" by a combination of MSB and naltrexone. Abstract: Alcohol relapse plays a major role in alcohol dependence and is an important focus for the treatment of alcoholism. The alcohol deprivation effect (ADE) is a widely used paradigm in rodents to model the relapse episodes that occur in human alcoholics. Mesyl Salvinorin B (MSB) is a potent and selective kappa opioid receptor (KOP-r) full agonist, with fewer side effects ( e.g ., sedation or anhedonia) than classic KOP-r full agonists and a longer duration of action in mice than the structurally similar salvinorin A. We have recently found that MSB prevents cocaine seeking in a rat self-administration model and reduces excessive alcohol drinking in a mouse escalation model via a KOP-r-mediated mechanism. Here, we further investigated whether MSB alone (0.3–3 mg/kg) or in combination with naltrexone (mu-opioid receptor antagonist at 1 mg/kg) altered alcohol "relapse" drinking using a mouse ADE paradigm. Both male and female mice, exposed to 3-week intermittent access alcohol drinking in a two-bottle choice paradigm with 24-h access every other day, developed excessive alcohol intake and then displayed pronounced ADE after 1-week abstinence. Acute administration of MSB prevented the ADE at 3 mg/kg in both male and female mice. Upon investigation of potential synergistic effects between naltrexone and MSB, we found that acute administration of a combination of MSB (0.3 mg/kg) and naltrexone (1 mg/kg) reduced the ADE at doses lower than those individual effective doses, with no sex difference. Our study suggests that the KOP-r full agonist MSB both alone and in combination with naltrexone shows potential in alcohol "relapse" treatment models.